A novel insulin delivery system by β cells encapsulated in microcapsules - Luo, Zongjie; Dong, Yutong; Yu, Mengyu; Fu, Xiao; Qiu, Yudong; Sun, Xitai; Chu, Xuehui (Frontiers in Chemistry, 2023)
Diabetes is a growing epidemic worldwide and requires effective clinical therapies. In recent years, β-cell transplantation has emerged as a promising treatment for diabetes, and an encapsulation approach has been proposed to ameliorate this treatment. Here, microfluidic technology had been used to generate microcapsules using a porous sodium alginate shell and a core containing β cells in less than half an hour, resulting in a high cell survival rate (>90%). Porous hydrogel shell allows exchange of small molecules of nutrients while protecting beta cells from immune rejection, while the core ensures high activity of the encapsulated cells. The potential of the living cell biological system as an artificial islet was further demonstrated after it was transplanted into the mesentery of diabetic mice to treat diabetes. We believe that this system, which is composed of biocompatible porous hydrogel shell and enables highly activity of encapsulated β cells, can enhance therapeutic efficacy and has promising clinical applications.